Use of the Discovery Learning Model to Improve the Integrated Thematic Learning Process: Penggunaan Model Discovery Learning untuk Meningkatkan Proses Pembelajaran Tematik Terpadu - Halida (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
This research is motivated by the low learning outcomes of Thematic Integrated Learning Theme 3. The research aims to describe the use of the Discovery Learning model to improve the integrated thematic learning process on theme 3. The research was conducted at SDN 03 Pulau Punjung. Subjects of teacher and class V students were 22 people. The results showed the learning outcomes of the first cycle an average of 75 and increased in the second cycle to 90.6. The results showed that the increase in the RPP cycle I meeting I got a value of 71.9% with sufficient qualifications (C), The increase occurred in cycle II to 93.75% with very good qualifications (SB) because the selection of materials was in accordance with student preferences, source selection learning is in accordance with the Discovery Learning model, the selection of learning resources is in accordance with the characteristics of students, and in the RPP is in accordance with the suitability of time in each learning activity.